Karakterisasi Massa Batuan dan Analisis Kestabilan Lereng Untuk Evaluasi Geometri Lereng di Pit Barat Tambang Terbuka PT. AICJ (Allied Indo Coal Jaya) Kota Sawahlunto Provinsi Sumatera Barat - Riski Adelina Pane; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2019)
Abstract.The stability of the mine slope is the most important factor that must be considered in the continuation of mining activities. Research sites on three mining slopes PT. AICJ, namely coordinates S00˚36'09.3”/E100˚48'16.3", coordinates S00˚43'27.0"/E100˚47'11,1" with slope height = 35m and slope = 63˚, and at coordinates S00˚36'09.7"/E100˚48'16.2" with slope height = 30m and slope = 63˚. The method used is Bishop and Hoek and Bray. As a result of research, the following conclusions are drawn. First, based on the analysis of RQD, RMR, and SMR rock types on location classified in the class fair rock-good rock. Second, the results of the analysis of single and overall slope of actual earned value FK at the coordinates I, II, and III = 1.280/1.225, 1.323/1.203, 1.308/1.203(natural conditions) and FK = 0.844, 0.905, 0.859(saturated condition). Third, to obtain a safe FK that is 1.25, the geometry of the slope is modified, namely coordinate with a slope height of 31 m and slope 49˚, coordinate II slope height 33 m and slope 50˚, and coordinate III of slope height of 25 m and slope 54˚ in saturated condition.Keywords :slope stability analysis,RQD, RMR, SMR, bishop method, hoek and bray method